On the solution of stochastic oscillatory quadratic nonlinear equations using different techniques, a comparison study - El-Tawil, Magdy A.; Al-Jihany, Amna S. (Topological Methods in Nonlinear Analysis, 2008)
In this paper, nonlinear oscillators under quadratic nonlinearity with stochastic inputs are considered. Different methods are used to obtain first order approximations, namely the WHEP technique, the perturbation method, the Pickard approximations, the Adomian decompositions and the homotopy perturbation method (HPM). Some statistical moments are computed for the different methods using Mathematica 5. Comparisons are illustrated by figures for different case-studies.